EP337 The philosophy of setinel lymph node in the management of early stage cervical cancer. Feasible or not?. (1st November 2019) - Koutroumpa, I; Thomakos, N; Sotiropoulou, M; Theofanakis, C; Theodoulidis, V; Pandraklakis, A; Vlachos, D-E; Haidopoulos, D; Rodolakis, A
Abstract : Introduction/Background: A single institution study developing a simple algorithm in sentinel lymph node (SLN) mapping, evaluating the detection rate and diagnostic accuracy between frozen section biopsy (FSB) and final histopathology (FH). We also present an attempt to assess SLN concept for less radical surgery in early stage cervical cancer (CaCx). Methodology: Prospective study including patients with CaCx, stage IA1–IIA1 (tumour size 0.5–3 cm). Intracervical injection of methylene blue after induction of anaesthesia, detection of LNs that are dyed and sent for FSB. Bilateral pelvic lymphadenectomy and radical hysterectomy is then performed and correlated with FH. Results: In our study, 70 patients were eligible. At least one SLN (range 0–6) was identified in 82.4% (58/70), whereas bilateral detection was succeeded in 80% (56/70). SLNs were located at the external (53.8%) or internal iliac region (15.4%), obturator fossa (19.2%), and ventral to the hypogastric vessels (11.6%), whereas 9.1% found in (unexpected) area (parametrium) in cases with tumour size (TS) ≥3 cm. Frozen section was positive in 4 cases (5.7%) and the procedure was aborted. Sentinel lymph node sensitivity in detection of metastasis was 100% for TS≤2 cm. False negative SLN and micrometastasis was identified in only two cases (TS>2 cm). Parametrial involvement was not detected when SLNs were negative. Conclusion: Our findings confirm the clinical significance of SLN mapping in minimizing systematic lymphadenectomy and supports less radical surgery of parametrium with greater safety. However, we are still in the process to establish our technique as feasible and equate in early stage cervical cancer. Disclosure: Nothing to disclose.